Polemicization : the contingency of the commonplace - Arditi, Benjamín (Taking on the political., 1999)
Covering the theories of, among others, Derrida, Lefort and Laclau, this volume opens up space to the political (polemicisation). Chapters cover themes such as social structure, ethical arguments, and political organisation.